P-751 Comparing LNG-IUS 52mg versus hysteroscopic resection in patients with postmenstrual spotting related to a niche in the caesarean scar (MIHYS NICHE Trial). (30th June 2022) - Zhang, D; Zhu, C; Yan, L; Xie, L; Huirne, J.A; Mol, B.W; Zhang, J
Abstract: Study question: Among women with niche-related postmenstrual spotting, is LNG-IUS 52mg superior to hysteroscopic niche resection? Summary answer: At the 6 th month after treatment, the median total bleeding days after LNG-IUS 52mg was 4 days, shorter than 13 days after hysteroscopic niche resection. What is known already: The rate of caesarean sections (CS) is growing worldwide and the prevalence of niche, one of complications of CS, has increased substantially. Until now, evidence-based clinical guidelines for the treatment of niche are few. In patients with niche-related postmenstrual spotting, there are some studies confirm the effectiveness of a levonorgestrel 52 mg intrauterine system (LNG-IUS) on the niche-related symptoms, while some retrospective studies indicated conflicting results. The effect of LNG-IUS and hysteroscopic niche resection in niche-related spotting has not been studied in any RCT yet. Study design, size, duration: This is a randomized controlled trial conducted in a university-based hospital from Dec 2019 to Jan 2021. Women who were suffering from niche-related postmenstrual spotting for more than two days and had no fertility intention in the coming 12 months were recruited. After randomisation for LNG-IUS 52mg or hysteroscopic resection, follow-up was performed at the 3 rd, 6 th, 9 th and 12 nd month. Based on our protocol, 208 women (104 in each group) were included. Participants/materials, setting, methods: After informed consent is obtained, eligible women were randomly allocated to LNG-IUS 52mg or hysteroscopic niche resection at 1:1. The primary outcome was the efficacy in reducing postmenstrual spotting at the 6 th month after randomisation. The secondary outcomes include menstrual pattern, total bleeding days per month, rate of amenorrhoea, side effects and complications. Student's t-tests were performed to compare the effective rate in improving postmenstrual spotting between two groups. Main results and the role of chance: 208 women were randomised, finally 101 patients in the LNG-IUS group and 104 in hysteroscopic resection group were included in the intention to treat analysis. Median reduced spotting days maintained within 5 days after hysteroscopic niche resection at the 3 rd, 6 th, 9 th and the 12 nd month, while after LNG-IUS treatment it increased from 4 days at the 3 rd month to 7 days at the 12 nd month. Participants reported a reduction of spotting days by at least 50% from baseline at one-year follow-up in 91 out of 101 (90.0%) in the LNG-IUS group versus 73 out of 104 (70.2%) in the hysteroscopic niche resection group (Relative Risk 1.3; 95% CI 1.1 to 1.5; p < 0.001). The effectiveness rate increased over time within 1 year after the insertion of LNG-IUS (58.4%, 78.2%, 89.1%, 90.0%, P for trend = 0.042), while no trend change was observed in hysteroscopy group (67.3%, 73.1%, 72.1%, 70.2%, P for trend = 0.625). In the LNG-IUS group, two women removed their IUS after expulsion and three did so after bleeding symptoms. In the hysteroscopy group, two women got pregnant. No serious complications were observed in either group. Limitations, reasons for caution: The trial was based in a single centre, which might limit the generalisability of the findings. Meanwhile, this trial was an open-label trial both for patients and for researchers, and a blind method was applied to evaluate the effect of treatment. Wider implications of the findings: LNG-IUS 52mg is superior to hysteroscopic niche resection in reducing niche related postmenstrual spotting from the 6 th month. LNG-IUS has advantages including contraceptive effect, no need for (general) anaesthesia or hospitalisation, easy to insert, fewer complications and lower cost. LNG-IUS should be recommended as the first choice for these women. Trial registration number: ChiCTR1900025677